2005
DOI: 10.1097/01.brs.0000179082.92712.89
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Single and Dual Growing Rod Techniques Followed Through Definitive Surgery

Abstract: The use of growing rods is effective in controlling severe spinal deformities and allowing spinal growth. Dual rods are stronger than single rods and, therefore, provide better initial correction and maintenance of correction. The use of an apical fusion does not appear to be effective over the course of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
131
1
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(142 citation statements)
references
References 14 publications
4
131
1
6
Order By: Relevance
“…The authors concluded that the dual growing rod technique was safe and effective, and had an acceptable rate of complications compared with previous reports while preserving near-normal growth [10]. Consistently better results have been reported with the use of double rods instead of a single one [11,12].…”
Section: Conception and Historysupporting
confidence: 52%
“…The authors concluded that the dual growing rod technique was safe and effective, and had an acceptable rate of complications compared with previous reports while preserving near-normal growth [10]. Consistently better results have been reported with the use of double rods instead of a single one [11,12].…”
Section: Conception and Historysupporting
confidence: 52%
“…The dilemma of simultaneously providing three-dimensional stability and enhancing growth in a mixed population of idiopathic, neuromuscular and syndromic disorders seems to be best challenged by dual growing rods [14,21]. However, the risk of placement and pull-out of pedicle screws in patients with small anatomy, repetitive surgery, the rigidity of fixation and a complication rate of 20% per surgery [10] promotes the search for alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…However, VEPTR's safety and efficacy remains still to be shown for non-congenital deformities. It thereby competes with a variety of established or evolving growth respecting methods such as serial casting [9], growing rods [10][11][12][13][14][15][16] and growth guiding implants [12,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, early fusion frequently was recommended for treatment of EOS [16]. However, there is a growing consensus that early spinal fusion results in negative thoracopulmonary consequences to children [15], and most surgeons now use fusion as a last resort in the young child. Hemiepiphysiodesis, hemivertebral resection, and short segment fusions continue to be used in selected patients.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of one report recommend placement of growing rod instrumentation on the concave side of the spine only to expand the smallest hemithorax [2], whereas others report better radiographic correction and fewer complications with bilateral constructs [15]. An opening wedge thoracostomy sometimes is performed as part of distraction thoracoplasty [10], but some surgeons prefer not opening the thoracic cavity as they are concerned by the potential for scarring and subsequent restriction this could cause [8].…”
Section: Introductionmentioning
confidence: 99%